2017
DOI: 10.3389/fmars.2017.00384
|View full text |Cite
|
Sign up to set email alerts
|

Marine Natural Products: New Avenue in Treatment of Osteoporosis

Abstract: Bone metabolism is a physiological process that maintains the skeletal integrity and bone functions. Skeletal integrity is always balanced by two key cell types-bone resorbing osteoclasts and bone-forming osteoblasts. Imbalance between generation and function of osteoclasts and osteoblasts often leads to pathological conditions such as osteoporosis, osteopetrosis, Paget's disease. Osteoporosis is one of the most common age-related diseases characterized by decreased bone mineral density and microarchitectural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 157 publications
0
13
0
Order By: Relevance
“…Uchiyama and Yamaguchi reported that the water-solubilized Sargassum horneri extract stimulates osteoblastic bone formation and suppresses osteoclastic bone resorption, exhibiting both osteogenic and anti-osteoclastogenic properties [15]. In addition, the extract of Padina Pavonica was shown to improve calcium uptake and is currently marketed as a dietary supplement to prevent osteoporosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Uchiyama and Yamaguchi reported that the water-solubilized Sargassum horneri extract stimulates osteoblastic bone formation and suppresses osteoclastic bone resorption, exhibiting both osteogenic and anti-osteoclastogenic properties [15]. In addition, the extract of Padina Pavonica was shown to improve calcium uptake and is currently marketed as a dietary supplement to prevent osteoporosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…OP is a silent disease which leads to feeble quality of life and increased mortality in aged people, especially in postmenopausal women [16]. The balance between bone resorption and bone formation is the key point in bone homeostasis and health and an imbalance of these events causes OP.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between bone resorption and bone formation is the key point in bone homeostasis and health and an imbalance of these events causes OP. Loss of bone matrix and mass and microarchitectural deterioration are the main features of OP that increase the rate of fractures [16]. Nowadays, finding the proper treatment for bone-related disease is a matter of great interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, natural products have been revisited as viable drug leads [18,19,29,30,31,32,33]. The renewed interest in natural products as drug leads is a combination of the improved ability for high-throughput screening of natural sources and the failure of combinatorial chemistry to deliver sufficient numbers of viable drug candidates [34,35].…”
Section: Introductionmentioning
confidence: 99%